Very Long Baseline Interferometry Techniques and Their Applications in Radio Astronomy Research - Zhou, Yuyang (Transactions on Computer Science and Intelligent Systems Research, 2024)
Radio astronomy plays a crucial role in advancing the understanding of space objects by utilizing radio waves, allowing us to observe phenomena and celestial bodies that are otherwise invisible when using traditional optical telescopes. This technique, called Very Long Baseline Interferometry (VLBI), combines signals from different radio telescopes to give a much clearer picture. This paper talks about how VLBI works, including how it picks up signals, measures time delays, and fine-tunes these signals. It’s especially useful for taking pictures of black holes and studying space jets, and it was crucial for the Event Horizon Telescope project. The research shows that VLBI improves how well it can see space and helps us learn about extreme conditions in the universe. Although there are challenges with sensitivity and handling the data, future improvements in technology and expanding into space could help us understand the universe even better. This study gives new ideas and directions for making VLBI technology better.